Seaport efficiency and productivity based on Data Envelopment Analysis and Malmquist Productivity Index - Baran Joanna; Górecka Aleksandra (Logistics & Sustainable Transport, 2015)
Seaport efficiency and productivity are the critical factors for handling of goods in the international supply chains and plays an important role in trade exchange with other countries. It is important to evaluate efficiency and productivity of seaports to reflect their status and reveal their position in competitive environment. The main purpose of this article is to use Data Envelopment Analysis and Malmquist Productivity Index to measure the technical efficiency and total factor productivity of container ports. DEA analysis enables one to assess how efficiently a seaports uses the available inputs to generate a set of outputs relative to other units in the data set. This article presents the use CCR and BCC DEA model, to determine overall technical efficiency, pure technical efficiency and scale efficiency of container ports. The analysis gives a possibility to create a efficiency ranking of seaports. The study also applies the Malmquist Productivity Index (MPI), which was used to analyze changes in seaports productivity. The study indicated that technological progress had a greater impact on the change in productivity of container ports than changes in technical efficiency.